Acetaminophen attenuates lipopolysaccharide-induced cognitive impairment through antioxidant activity - Zhao, Wei-Xing; Zhang, Jun-Han; Cao, Jiang-Bei; Wang, Wei; Wang, Dong-Xin; Zhang, Xiao-Ying; Yu, Jun; Zhang, Yong-Yi; Zhang, You-Zhi; Mi, Wei-Dong (Journal of neuroinflammation, 2017)
Background Considerable evidence has shown that neuroinflammation and oxidative stress play an important role in the pathophysiology of postoperative cognitive dysfunction (POCD) and other progressive neurodegenerative disorders. Increasing evidence suggests that acetaminophen (APAP) has unappreciated antioxidant and anti-inflammatory properties. However, the impact of APAP on the cognitive sequelae of inflammatory and oxidative stress is unknown. The objective of this study is to explore whether APAP could have neuroprotective effects on lipopolysaccharide (LPS)-induced cognitive impairment in mice. Methods A mouse model of LPS-induced cognitive impairment was established to evaluate the neuroprotective effects of APAP against LPS-induced cognitive impairment. Adult C57BL/6 mice were treated with APAP half an hour prior to intracerebroventricular microinjection of LPS and every day thereafter, until the end of the study period. The Morris water maze was used to assess cognitive function from postinjection days 1 to 3. Animal behavioural tests as well as pathological and biochemical assays were performed to evaluate LPS-induced hippocampal damage and the neuroprotective effect of APAP. Results Mice treated with LPS exhibited impaired performance in the Morris water maze without changing spontaneous locomotor activity, which was ameliorated by treatment with APAP. APAP suppressed the accumulation of pro-inflammatory cytokines and microglial activation induced by LPS in the hippocampus. In addition, APAP increased SOD activity, reduced MDA levels, modulated glycogen synthase kinase 3β (GSK3β) activity and elevated brain-derived neurotrophic factor (BDNF) expression in the hippocampus. Moreover, APAP significantly decreased the Bax/Bcl-2 ratio and neuron apoptosis in the hippocampus of LPS-treated mice. Conclusions Our results suggest that APAP may possess a neuroprotective effect against LPS-induced cognitive impairment and inflammatory and oxidative stress via mechanisms involving its antioxidant and anti-inflammatory properties, as well as its ability to inhibit the mitochondrial permeability transition (MPT) pore and the subsequent apoptotic pathway.